Changing Building Sites: Industrialisation and Automation of the Building Process. (May 2014) - Bock, Thomas; Langenberg, Silke; Gramazio, Fabio; Kohler, Matthias
Abstract The introduction of robotics in construction is part of a much longer history of industrialisation and automation on the building site. Thomas Bock of the Technical University of Munich and Silke Langenberg of the University of Applied Sciences, Munich, highlight how the Industrial Revolution and the development of a transport infrastructure in the 18th and 19th centuries in Europe first triggered the shift in the building trade from a largely localised industry into a national and mechanised one, leading to the highly advanced automated construction techniques that continue to be developed in Japan and other Asian countries to this day.